BOOK REVIEW INDONESIAN LAW - Irawaty, Rosewitha (Indonesia Law Review, 2019)
The authors have presented a snapshot of Indonesia’s legal system in a manner that breaks down the justification, significance and definitions of the country’s past and existing laws. Delivered in the format of a monograph, Lindsey and Butt were able to masterfully deduce as well as extract key points relating to the basic foundation of the country’s laws. The book underlines the importance of understanding history before delving into the law, such is the case in the book’s writing on the Constitution, in which the country’s state ideology was first explained and its developments detailed through the account of Indonesia’s formative years.